Otimização na alocação dinâmica de veículos no transporte rodoviário de cargas completas entre terminais - Vasco, Rejane Arinos (2012)
The domain of logistics is concerned with providing customers with the right product in the right place at the right time. In our modern economy, the faster pace and wider scope of logistic operations has led to complex management problems that have drawn the attention of both industry and the academic world Optimizing the number of vehicles for a determined transport system requires a trade-off between the cost of vehicle acquisition and maintenance and the penalties involved in not meeting the requirements of the system. This thesis proposes to contribute to decision making in the operational management of those companies working in the transportation of goods by road, particularly as regards the optimization of vehicle use in freight transfer between terminals. Various operational problems, especially management of the transfer fleet, involves the dynamic allocation of limited resources to meet demand. Specifically, this paper deals with the dynamic (multi-period) vehicle allocation problem (DVAP) in the road transportation of full loads between terminals. The DVAP belongs to that class of problems dealing with dynamic resource allocation and consists of defining the movements of a fleet of vehicles that transport goods between terminals with a wide geographical distribution and which interact among themselves. These movements may be of fully-laden vehicles, unladen vehicles for repositioning or vehicles held at a terminal to meet future demands. Emphasis is given to the characterization of the problem in real situations, mathematical modeling of the problem and the use of operational research techniques in solving the problem. Also, heuristics and metaheuristics such as GRASP, simulated annealing and ant colony optimization are used in the solution. The objective is to determine dynamic allocation and fleet needs in order to minimize operational costs in meeting the demand for services. The main reason for undertaking this work was the possibility of practical application, the development of integer linear programming models and both exact and heuristic methods for solutions, aiming at the practical validation of the approaches in the real operational environment of a Brazilian transport company.